1995
DOI: 10.1073/pnas.92.16.7401
|View full text |Cite
|
Sign up to set email alerts
|

Multimeric complexes of the PML-retinoic acid receptor alpha fusion protein in acute promyelocytic leukemia cells and interference with retinoid and peroxisome-proliferator signaling pathways.

Abstract: The t(15;17) chromosomal translocation, specific for acute promyelocytic leukemia (APL), fuses thePML gene to the retinoic acid receptor a (RARa) gene, resulting in expression of a PML-RARa hybrid protein. In this report, we analyzed the nature of PML-RARa-containing complexes in nuclear protein extracts of t(15;17)-positive cells. We show that endogenous PML-RARa can bind to DNA as a homodimer, in contrast to RARa that requires the retinoid X receptor (RXR) dimerization partner. In addition, these cells conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 22 publications
2
65
0
1
Order By: Relevance
“…In vitro studies have demonstrated that PML-RARa and PLZF-RARa disrupt the transactivating e ects of RARa at the RAREb 2 promoter, and that the dominant negative e ects of PML-RARa and PLZFRARa are reversed in the presence of ectopically expressed RXRa Licht et al, 1996). PML-RARa and PLZF-RARa heterodimerize with RXRa through the RARa dimerization domain retained in the RARa portion of the fusions (Jansen et al, 1995;Licht et al, 1996). Recently it has been shown that both PML-RARa and PLZF-RARa silence the transcription of RA responsive genes under physiological concentrations of RA (Grignani et al, 1998;He et al, 1998;Lin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that PML-RARa and PLZF-RARa disrupt the transactivating e ects of RARa at the RAREb 2 promoter, and that the dominant negative e ects of PML-RARa and PLZFRARa are reversed in the presence of ectopically expressed RXRa Licht et al, 1996). PML-RARa and PLZF-RARa heterodimerize with RXRa through the RARa dimerization domain retained in the RARa portion of the fusions (Jansen et al, 1995;Licht et al, 1996). Recently it has been shown that both PML-RARa and PLZF-RARa silence the transcription of RA responsive genes under physiological concentrations of RA (Grignani et al, 1998;He et al, 1998;Lin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to RARa that requires the retinoid X receptor dimerization partner to e ciently bind DNA (Mangelsdorf and Evans, 1995a), PML-RARa can bind target sequences as a homodimer with distinct DNAbinding properties suggesting that it may interfere with other nuclear receptor pathways (Perez et al, 1993;Jansen et al, 1995). In this regard, it has been shown that the fusion protein is able to block the vitamin D3-induced di erentiation of U937 cells (Grignani et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of catabolism of the fusion protein is quite variable (Duprez et al, 1996a,b;Jansen et al, 1995;Raelson et al, 1996;Yoshida et al, 1996;Zhu et al, 1997Zhu et al, , 1999. Degradation of the fusion protein is clearly responsible for the RA-induced relocalization of PML (and associated NB proteins) (Daniel et al, 1993;Dyck et al, 1994;Koken et al, 1994;Weis et al, 1994), which could promote apoptosis induction.…”
Section: The Playersmentioning
confidence: 99%
“…A Ā®rst mechanistical analysis demonstrated that caspase activation was responsible for cleavage of the fusion protein , accounting for the appearance of a de novo 90 kD protein upon RA exposure (Duprez et al, 1996a;Gianni et al, 1998;Jansen et al, 1995;Raelson et al, 1996;Zhu et al, 1999). The speciĀ®c cleavage site was mapped to the Cterminus of PML (D522).…”
Section: The Playersmentioning
confidence: 99%